CULTIVATING HARD-WORKING AND PEACE-LOVING CHARACTER THROUGH THE TAPAK SUCI EXTRACURRICULAR ACTIVITIES - Lias Arita Safa; Arief Cahyo Utomo (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
Abstract This study aims to analyze how to cultivate the character of hard-working and peace-loving in tapak suci, as well as describe its inhibiting factor and solution. This research used a descriptive qualitative approach. The research subjects were the students of MIN 5 Sragen. Data collection techniques were through observations, interviews, and documentation. Data validation in this study used data triangulation techniques by reducing data, presenting data, and drawing conclusions. The results of this study indicated that cultivating hard-working and peace-loving character in tapak suci as an extracurricular activity at MIN 5 Sragen was carried out by instilling and obeying the rules that had been notified by the coach and warming up before training. The inhibiting factor in cultivating these characteristics was the lack of facilities provided by the school, thus the solution was that the school needed to maximize facilities by asking for help from PEMDA.